2015
DOI: 10.1093/annonc/mdv107
|View full text |Cite
|
Sign up to set email alerts
|

Survival in stage I–III breast cancer patients by surgical treatment in a publicly funded health care system

Abstract: Background: Recent investigations of breast cancer survival in the United States suggest that patients who receive mastectomy have poorer survival than those who receive breast-conserving surgery (BCS) plus radiotherapy, despite clinically established equivalence. This study investigates breast cancer survival in the publicly funded health care system present in Alberta, Canada.Patients and methods: Surgically treated stage I-III breast cancer cases diagnosed in Alberta from 2002 to 2010 were included. Demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
55
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 21 publications
5
55
0
2
Order By: Relevance
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our results further support the hypothesis that BCT might be the preferred choice for breast cancer patients when both BCT and mastectomy are suitable treatment options . A previous observational study that also investigated survival outcomes following both types of surgery hypothesized that the prognostic advantage of BCT over mastectomy may be related to the effects of RT as a component of BCT while early stage mastectomy patients in general receive no RT5.…”
Section: Discussionsupporting
confidence: 84%
“…A possible explanation for the differences in BCSS between the two time cohorts, apart from the difference in the applied chemotherapy regimens, is the length of follow‐up. Recurrence peaks (including local/locoregional recurrences and distant metastases) are described to occur 2, 5 and 9 years after diagnosis . Since the 2006–2012 cohort had a median follow‐up of 7 years, this cohort may have had too short follow‐up to reveal the effect of BCT and mastectomy after 7 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple randomized studies have demonstrated that breastconserving therapy (partial mastectomy plus whole breast radiation) can yield survival outcomes equivalent to those of mastectomy (1). However, newer population-based data suggest that breast cancerespecific survival and overall survival with breast-conserving therapy may actually be better than those with mastectomy (2)(3)(4)(5)(6)(7)(8). How is this possible?…”
mentioning
confidence: 99%
“…We suggest that adjuvant RT may have a more important role when surgical practice evolves to reduce the volume of tissue resected during breast and axillary surgery. The integral role of adjuvant RT in breast-conserving therapy may explain why it is associated with better breast cancerespecific survival and overall survival relative to mastectomy in several recent population-based studies (2)(3)(4)(5)(6)(7)(8). This improvement in survival is strongest in earlystage subgroups (in which postmastectomy RT is seldom used) and in those with comorbiditiesdfor whom systemic chemotherapy is less often applied (2, 4, 8)dsuggesting possible multimodality interactions.…”
mentioning
confidence: 99%